Dampak Kenaikan Tarif Bahan Bakar Minyak Terhadap Aspek Pendapatan Nelayan Pancing Tonda Di Pesisir Kota Ambon, Provinsi Maluku - Tawari, Ruslan H. S.; Tuhumury, Julian; Hehanussa, Kedswin G.; Umacina, Rahmiyanti (Cenderawasih University, 2024)
The rising cost of petalite fuel oil is causing concern for small-scale fishermen, particularly trolley fishermen, in the coastal regions of Ambon City. The public has expressed frustration with the increase, as it has the potential to raise the cost of living and necessities. This study aims to provide a more in-depth understanding of the issue and offer recommendations for Ambon City's fishermen in response to the government's frequent fuel price hikes. The research was conducted between November 2022 and January 2023 using observation and interview methods, along with questionnaires. Ambon City fishermen primarily use diluted Pertalite fuel, which costs IDR 15,000 in Laha, Hative Besar, and Latuhalat villages, and Rp 13,000 in Seri Village. Fishermen from different villages use differing amounts of fuel, with Laha Village fishermen using 20 liters per trip, Hative Besar Village using 5 liters, Latuhalat Village using 60 liters, and Seri Village using 40 liters. Comparing the income before and after the fuel increase, the results indicate that fishermen's income decreased after the fuel increase, with a decrease percentage of 47.12%